The Specialist Nurse as a Leader: Mapping Leadership in Specialist Nursing Programs in Sweden - Areskoug Josefsson, Kristina (Nordisk Tidsskrift for Helseforskning, 2025)
Specialist nurses have important roles as leaders to promote health. Further development of nurse leadership education is required to meet the needs of society, and to address the complexity between quality of care and cost-effectiveness. This study explored how leadership is presented and exemplified in specialist nursing programs, and how this can affect the understanding and practice of specialist nurse leadership. A document analysis was conducted of course syllabi from leadership courses of Swedish specialist nursing programs. The results show that leadership could be more present in descriptions of specialist nursing education, to further highlight the role of the specialist nurse as a leader and driver of innovation, organizational learning, and continuous professional development. A clear focus on leadership in educational documents can promote understanding of nurse leadership. There is development potential in nurse leadership education, to meet the complexity and needs of nursing leadership of today’s more business-oriented healthcare.